Wpływ Waltera Scotta na prozę historyczną Aleksandra Puszkina: „Rob Roy” i „Córka kapitana” - Kizelbach, Urszula (Studia Rossica Posnaniensia, 2016)
This article analyses the influence of Sir Walter Scott’s historical fiction (Rob Roy) on the development of the historical novel in Russia in the first half of the 19th century, based on the example of Pushkin’s The Captain’s Daughter. The author argues that both Scott and Pushkin had a similar approach to their national and local history and collected historical material in the same way (through archival research and by contacting local people who had witnessed the events of the Jacobite Rebellion, 1715, and the Pugachev Rebellion, 1773–1775). A close analysis of both texts presents examples of a similar poetics of the narration, dialectal use of language and dialogue, and the use of local colour and folk elements, such as folk songs or old sayings, which serve as mottos for particular chapters in the novels.